PENGARUH PEMBERIAN EDUKASI BANTUAN HIDUP DASAR TERHADAP KESIAPAN PERTOLONGAN TENGGELAM PADA PEKERJA DI WISATA AIR KERAMAS PARK - Windari, Ni Wayan; Saputra, I Kadek; Damayanti S, Made Rini (Coping: Community of Publishing in Nursing, 2021)
Tourism activities in swimming pools are at risk of drowning accidents that require assistance in the form of basic life support (BLS) by water tourism workers. However, not all of water tourism workers know the technique of giving BLS. So, the education that focuses on BLS assistance is very important for water tourism workers to increase readiness for BLS assistance. This study aims to find out the effect of providing basic life support education on drowning aid readiness of workers in the Keramas Park water tourism area. Th e type of research is a pre-experimental design with a one group pre-test and post-test design involving 23 respondents who were taken by total sampling technique. The intervention provided was in the form of blended B LS education, namely the online method by providing material (power point materials, learning modules, and practical operational standards ) through WhatsApp groups, then offline education by conducting lectures and B LS simulations using mannequins. Respondents were given the opportunity to practice B LS . Readiness data was measured using a questionnaire given before and after BHD education. The results of descriptive data analysis showed that the average age of the respondents was 32 years with a length of work 2.91 years with a median pre-test value of 37.00 and a post-test value of 60.00. Bivariate analysis using the Wilcoxon test with a confidence level of 95% (? = 0.05) obtained a significance value of 0.000. It can be concluded that BLS education can increase the readiness of drowning rescue workers in Keramas Park water tourism. Researchers recommend to conduct regular BLS education for workers at Keramas Park water tourism. Keywords: Basic Life Support Education (BLS), Drowning Accidents , Readiness